Morphological and histological kidney structure in diabetic rats model treated with ethanol extracts of jengkol fruit peel (Archidendron pauciflorum) - Malini, Desak Made; Fitriani, Nurullia; Laila, Adnin; Ratningsih, Nining; Setiawati, Tia (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANA, 2021)
In a long term, diabetes mellitus (DM) leads to nephropathy due to glomerular hyperfiltration. One of the plant used as a diabetic drug by the community in Karangwangi Village, Cianjur Regency, West Java is the fruit peel of jengkol. Therefore, this study aims to determine the effect of the ethanolic extract of Jengkol fruit peel (EEJFP) toward the morphological and histological structure on the kidney of the diabetic rat model. The method adopted was the Randomized Design (CRD) with 6 treatments namely NC (Carboxyl Methyl Cellulose (CMC) 0.5%), PC (CMC 0.5%), Pb (Glibenclamide 5 mg/kg BW), P1, P2, and P3 (EEJFP 385; 770; and 1,540 mg/kg BW) with 4 replications for 14 consecutive days. Furthermore, the induction of diabetes with streptozotocin dose of 60 mg/Kg BW was performed intravenously in experimental animals except for the NC group. The parameters observed include relative weight, morphological, and histological structure of kidney which include glomerular diameter, Bowman space distance, and percentage of proximal tubular cell necrosis. The non-parametric and parametric data were tested by Kruskal Wallis and ANOVA test as well as Duncan's follow-up test, respectively. The results showed that there was no significant difference in the morphological structure of the kidney between treatment groups.  Furthermore, the relative weights of kidney in the PC, Pb, P1, and P3 groups were larger and significantly different compared to NC and P2 also, the histological structure showed that the glomerular diameter (65.43 ± 0.7 m), Bowman space distance (4.19 ± 1.7 µm), and the percentage of proximal tubular cell necrosis (24.6 ± 5.5%) at P2 were not significantly different from NC. Based on this results, it was concluded that EEJFP has no effect on the kidney’s morphological structure, however, it decreases its relative weight and repair the kidney’s histological damage of the diabetic rat model with the optimum dose of 770 mg/kg BW.